AI Use in Mathematics Education: Applications, Benefits, and Challenges - Dhakal, Bed Prasad (Mangal Research Journal, 2025)
The study explores the emerging role of Artificial Intelligence (AI) in mathematics education by systematically reviewing recent empirical and conceptual research published between 2020 and 2025. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, fourteen relevant articles were selected through defined screening and evaluation procedures. The review identifies three major applications of AI in mathematics education— personalized learning, problem-solving support, and content generation—and three major benefits, namely enhanced learning engagement and motivation, deeper conceptual understanding, and improved accessibility and convenience. Likewise, three critical challenges are recognized: issues of accuracy and reliability, reduced human interaction, and misalignment with existing curricula. The findings suggest that while AI presents transformative potential in mathematics teaching and learning, its integration should be grounded in pedagogical reflection, ethical awareness, and curriculum innovation. The study concludes that AI, when thoughtfully integrated with human intelligence, can reshape mathematics education toward more interactive, inclusive, and learner-centered practices.